Analisis Nilai-Nilai Pendidikan Karakter Dalam Buku Ilmu Pengetahuan Alam Kelas III Sekolah Dasar Terbitan Pusat Perbukuan Tahun 2008 - Liany, Elinda Dai Mitra, Drs. Mulyadi Sri Kamulyan, S.H.,M.Pd (2017)
This study aims to: 1) describe the values of character education in Natural Sciences Book Class III Primary School Published by Pusat Perbukuan of 2008 2) describe the advantages and disadvantages Natural Sciences Book Class III Primary School Published by Pusat Perbukuan of 2008. This type of research is descriptive qualitative research. The data in this study in the form sentences that show character values. Data collected by using read, see, and record. Data analysis technique used is content analysis. Found values of character education in Natural Sciences Book Class III Primary School Published by Pusat Perbukuan of 2008, among others: (1) Religious, (2) To be honest, (3) tolerance, (4) Discipline, (5) Hard work ( 6) Creative (7) Curiosity (8) Love the homeland (9) Appreciating the achievements (10) Friendly / communicative (11) Love peace (12) Joy of reading (13) Care for the environment (14) Caring social, and (15 ) Responsible. Meanwhile, Natural Sciences Book Class III Primary School Published by Pusat Perbukuan of 2008 values of character education that can not be found, among other things: (1) Independent, (2) democratic and (3) the National Spirit. In addition, the advantages and disadvantages of the four components of the book look at the preparation of the book, namely the feasibility of the content, language feasibility, feasibility presentation and feasibility graphic.